Antiviral Potential of Spondias mombin L. Leaves Extract Against Herpes Simplex Virus Type-1 Replication Using In Vitro and In Silico Approaches - Siqueira, Emerson M. da S.; Lima, Tábata L. C.; Boff, Laurita; Lima, Sarah G. M.; Lourenço, Estela M. G.; Ferreira, Éder G.; Barbosa, Euzébio G.; Machado, Paula R. L.; Farias, Kléber J. S.; Ferreira, Leandro de S.; Rocha, Hugo A. de O.; Simões, Cláudia M. O.; Zucolotto, Silvana M. (Planta Medica, 2020)
Spondias mobin leaves have been traditionally used for treating cold sores. The study investigated the mechanism of antiherpes action of S. mombin extract, fractions, and geraniin. Different concentrations of samples were used to evaluate the in vitro antiherpes activity (anti-HSV-1) in virucidal, post-infection, attachment, and penetration assays. The mechanism of action of geraniin was investigated considering the glycoproteins gB and gD of HSV-1 surface as potential molecular targets. Molecular docking simulations were carried out for both in order to determine the possible binding mode position of geraniin at the activity sites. The binding mode position was posteriorly optimized considering the flexibility of the glycoproteins. The chemical analysis of samples was performed by LC-MS and revealed the presence of 22 substances, which are hydrolysable tannins, O-glycosylated flavonoids, phenolic acids, and a carbohydrate. The extract, tannin-rich fraction and geraniin showed important in vitro virucidal activity through blocking viral attachment but showed no relevant inhibition of viral penetration. The in silico approaches demonstrated a high number of potential strong intermolecular interactions as hydrogen bonds between geraniin and the activity site of the glycoproteins, particularly the glycoprotein gB. In silico experiments indicated that geraniin is at least partially responsible for the anti-herpes activity through interaction with the viral surface glycoprotein gB, which is responsible for viral adsorption. These results highlight the therapeutic potential of S. mombin anti-herpes treatment and provides support for its traditional purposes. However, further studies are required to validate the antiviral activities in vivo, as well as efficacy in humans.
Keywords: Anacardiaceae; Spondias mombin; antiviral; herpes; tannins; geraniin; medicinal plant